Analisis Tingkat Pemahaman Masyarakat Terhadap Produk Pembiayaan Kredit Pemilikan Rumah ( KPR ) Pada Bank DKI Syariah Kantor Cabang Pembantu (KCP ) Matraman - Suci Rahmadani; Agus Salim; Hartini Salama (DPW FORSILADI SULSEL, 2025)
Abstract This study aims to analyze the level of public understanding of the Home Ownership Loan (KPR) products offered by Bank DKI Syariah KCP Matraman. Given the importance of a good understanding of sharia mortgage products, this study focuses on aspects that affect people's understanding, such as knowledge of sharia principles, product benefits, and the mortgage application process. Data was collected through a survey involving respondents from the community around KCP Matraman, who have or have the potential to use sharia mortgage products. The results of the study show that the level of public understanding of sharia mortgage products at Bank DKI Syariah KCP Matraman is at a moderate level, with several factors such as ineffective socialization and low Islamic financial literacy being the main obstacles. These findings indicate the need to increase education and socialization about sharia mortgage products to increase public understanding, which is ultimately expected to increase interest and use of these products